Anti-hyperlipidemic activities of Amauroderma rugosum on human hepatocellular carcinoma cells / Chan Kam Seng - Chan , Kam Seng (2018)
Cardiovascular disease (CVD) is a tender killer leading to an increased mortality level in most industrially-developed countries. The fruiting bodies of the Amauroderma rugosum (AR) has been proclaimed to have excellent cardiovascular benefits such as high antioxidative capacity, anti-hyperlipidemic, anti-hypertensive, anti-inflammatory, antiplatelet aggregation and anti-thrombotic effects. In the present study, we have investigated the anti-atherosclerotic potentials by measuring the in vitro antioxidant capacity, anti-hyperlipidemic, lipoprotein modulating activity and its related mechanism(s) in oleate-induced HepG2 cells. The semi-polar ethyl acetate extract (EA) demonstrated the highest antioxidant capacity. Besides, the EA also exhibited the strongest inhibitory effect on Cu2+-induced low-density lipoprotein (LDL) oxidation, and 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase activity, respectively. Meanwhile, other AR extracts were non-cytotoxic (IC50 > 100 μg/mL) to normal human hepatic (WRL 68) and human lung fibroblast (MRC-5) cells. Assay on lipid lowering effects revealed that oleate-induced HepG2 cells treated with EA showed pronounced reductions in intracellular accumulation and secretion of total cholesterol (TC) and total triglyceride (TG). Further investigation on oleate-induced HepG2 cells treated with EA has observed a down-regulation of sterol-regulatory element binding factor-2 (SREBF-2) which confirmed the inhibition on mevalonate-mediated biosynthetic pathway of cholesterol. Unpredictably, our results showed an up-regulation of sterol-regulatory element binding factor-1 (SREBF-1) which does not correspond to the decreased endogenous synthesis of triglyceride. Further evaluation on two other key lipid regulatory transcription factors demonstrated a dose-and time dependent co-enhanced liver X receptor alpha (LXR-α) and peroxisome proliferator-activated receptor alpha (PPAR-α) that suppressed the SREBF-1 promoting activity and SREBF-2 gene. The activation of LXR-α was further confirmed by the over expression mRNA levels of its target genes i.e., apolipoprotein E (APOE), cholesteryl ester transfer protein (CETP) and SREBF-1. However, our results showed up regulation of CETP and APOE at transcription level but a down regulation at translational level leading to dose-and time-dependently inhibited secretion of both CETP and apoE which is beneficial to regress cardiovascular response. Up-regulation of LXR-α has been the hallmark of the beneficial reverse cholesterol transport (RCT) pathway which raises the “good cholesterol”, the high-density lipoprotein (HDL) in the plasma. Further examination on two selected markers, i.e., apoA-1 and lecithin: cholesterol acyltransferase (LCAT) enzyme has evidenced the activation of RCT-related pathway leading to the over expression of HDL. On the contrary, down regulation of apoB-100, apoE, and CETP suppressed the production of “bad cholesterol”, LDL and very low-density lipoprotein (VLDL). Finally, ten phenolic compounds were identified by Liquid Chromatography-Tandem Mass Spectrometry analysis. Among those, caffeic acid (CA), protocatechuic acid (PCA), vanillic acid (VA), and 4-hydroxybenzoic acid (4HBA) were selected as bioactive markers. The dosedependent reduction of intracellular and secreted TC and TG demonstrated by CA, PCA, VA and 4HBA has evidenced their role in the lipid lowering effect. In summary, EA showed good anti-atherogenic potential through its high antioxidant capacity, antihyperlipidemic activity, and its lipoprotein modulating effect via activating the RCTmediated pathway in raising the HDL while suppressing the LDL and VLDL productions. Therefore, EA can be used as a source of anti-atherosclerotic agent for the prevention of cardiovascular diseases.